Energy and the environment in China : options for energy efficiency improvement and environmental pollution abatement in energy intensive and polluting industries - Wang, Yu; Chen, Xavier; Mohanty, Brahmanand; Stoll, Uwe; Yu, Cun Yi; Government of France (Bangkok : Asian Institute of Technology, 1995)
China is among the fastest growing economies in the world. The high economic growth is causing the high growth in energy consumption on one hand and environment degradation on the other. Iron and steel, cement, pulp and paper are three of the most energy intensive and polluting industries in China. In this study, we have presented sector by sector the evolution of technology, energy consumption pattern, energy efficiency and the situation of environmental pollution in the three selected industries. For each industry, an analysis of the determining factors of energy efficiency has been carried out. Energy efficiency of each industry is analyzed in relation with technological level, production structure, ownership of enterprises, as well as fuel and raw material mixes. The potentials for improving energy efficiencies of the three industries are assessed by comparing the major energy efficiency indicators with those of industrialized countries. Then a cross-industry comparison on the common and different determinants of energy efficiency among the three industries has been conducted. It is found that the energy efficiency level and the pollution situation of these industries are mainly related to the production scale and ownership status of enterprises, technological level, as well as raw material and energy mixes. A large number of small size township enterprises in cement and paper production lowers the energy efficiency and makes the pollution prevention and control very difficult. Based on the above, options for energy efficiency improvement and pollution abatement in the three industries through technological, economical, managerial and institutional means have been examined.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Energy consumption -- Environmental aspects -- China